2022
DOI: 10.54957/jurnalku.v2i4.312
|View full text |Cite
|
Sign up to set email alerts
|

Simulasi Perhitungan Analisis Standar Belanja Sebagai Dasar Penyusunan RKA-SKPD Pada Pemerintah Kabupaten Banyuasin

Abstract: Analisis Standar Belanja (ASB) merupakan pedoman yang digunakan untuk menganalisis kewajaran biaya dari anggaran belanja program atau kegiatan yang dilakukan oleh SKPD dalam satu tahun anggaran. Penggunaan ASB ini ditujukan agar APBD yang disusun memperhatikan asas umum pengelolaan keuangan daerah yaitu keadilan, kepatutan, dan manfaat bagi masyarakat. Tujuan penelitian ini untuk melakukan simulasi dalam menyusun ASB untuk kegiatan Penyusunan Laporan Keuangan SKPD di lingkungan Pemerintah Kabupaten Banyuasin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other research has also found that the preparation of RKA-SKPD has a positive impact on the survival of an SKPD organization (Pasi et al, 2018). In addition, other studies have found that the mechanism for preparing the RKA-SKPD is carried out in an orderly manner by carrying out according to the rules that have been set, and the accountable principle in which the mechanism for preparing the RKA-SKPD is carried out with transparency and accountability (Karim et al, 2021;Hakim & Hamzah, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has also found that the preparation of RKA-SKPD has a positive impact on the survival of an SKPD organization (Pasi et al, 2018). In addition, other studies have found that the mechanism for preparing the RKA-SKPD is carried out in an orderly manner by carrying out according to the rules that have been set, and the accountable principle in which the mechanism for preparing the RKA-SKPD is carried out with transparency and accountability (Karim et al, 2021;Hakim & Hamzah, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Every organization, including the central and regional governments, in carrying out their duties, is required to have a plan prepared and used as a guideline when carrying out their duties. Therefore, the government formulates various policies that are regulated in the form of a budget (Hakim & Hamzah, 2022). In the budget, it will be seen how big the function of the government is in carrying out various government affairs for which it is responsible and what factors can influence it (Manoppo & Walandouw, 2019).…”
Section: Introductionmentioning
confidence: 99%